GCT-22. OUTCOMES OF CHILDREN WITH LOCALIZED AND METASTATIC GERMINOMA TREATED WITH CHEMOTHERAPY FOLLOWED BY RADIATION THERAPY WITHOUT PRIMARY TUMOR BOOST. (3rd June 2022) - Bajin, Inci Yaman; Foo, Jen Chun; Bouffet, Eric; Ertl-Wagner, Birgit; Tsang, Derek; Laperriere, Norman; Dirks, Peter; Drake, James; Bartels, Ute
Abstract: BACKGROUND: Response-based radiation therapy has been the approach for germinoma after chemotherapy. However, the presence of residual lesions at the end of chemotherapy did not demonstrate a negative impact on progression-free survival (PFS). Similarly, resection of residual tumors after chemotherapy did not show a survival benefit. AIM: Our study objective was to determine long-term outcomes of a cohort who received chemotherapy and radiation therapy without primary tumor boost even in the absence of complete response to chemotherapy. METHOD: This retrospective study analyzed the outcome of germinoma patients diagnosed and treated at a tertiary care center from January 2006 to December 2021. RESULTS: Twenty-nine children (14 male; median age 12.8 years) were identified. Median follow-up was 63 months (range 9-187 months). Twenty children had localized disease and tumor location was suprasellar (n= 9), pineal (n= 10), and bifocal (n= 1) while 9 children had metastatic disease at presentation. All patients completed multi-agent chemotherapy followed by either whole ventricular (WVI) (23.4 Gy) (n = 23), whole brain (WBI) (23.4 Gy) (n = 5) or craniospinal radiation (CSI) (23.4 Gy) (n= 1). Two children, who had localized disease at presentation and received WVI after chemotherapy, relapsed 9 months and 32 months after completion of treatment respectively. None of them had local relapses. Location of relapse was distant, outside (n= 1) and inside (n= 1) the radiation field. Five-year PFS was 93% and overall survival (OS) was 100%. CONCLUSION: In this limited experience, excellent 5-year PFS and OS rates were achieved with chemotherapy followed by radiation therapy delivered without primary tumor boost. This study also demonstrated the absence of local relapse despite omitting primary tumor boost in patients with localized and metastatic germinoma.